Cinema Square Di Pekanbaru Dengan Pendekatan Arsitektur Postmodern - Fitrah Ramadhani Syam; Muhammad Rijal; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Cinema square is a surrounding which has some activities inside the open area such as theatre and plaza. Cinema is included to someone’s choice to free from full activity. The unres tricted style of this cinema square is coherent to the design principlies of postmodern architecture. Postmodern architecture emerged as a liberation act of modern architecture. By using postmodern architecture as an approachment to design Cinema Square in Pekanbaru, therefore the concept of "Freedom of Exspression" is obtained. The concept is applied by using metaphor approachment in zoning pattern, arrangement of the mass, outdoor space planning, mass forms, and facades. The outcome of the concept applied on zoning patterns is centrally formed, with mass arrangement in accordance to its functional behaviour, hence outer area arrangement will go along with mass arrangement. On the mass shaping wich is based on this square pattern gives a curving result on every building shoupe wich surrounds the site centrally. Where as the application on the facade is square line that lies horizontally on every building, this is intended as a modern form that can’t be separated from postmodern.Keywords: Cinema Square, Freedom of Expression, Metaphor, Postmodern Architecture.